Guess What …?—How Guessed Norms Nudge Climate-Friendly Food Choices in Real-Life Settings - Amelie Griesoph; Stefan Hoffmann; Christine Merk; Katrin Rehdanz; Ulrich Schmidt (Sustainability, 2021)
Social norms, also called social comparison nudges, have been shown to be particularly effective in promoting healthy food choices and environmentally friendly behaviors. However, there is limited evidence on the effectiveness of these nudges for promoting sustainable and climate-friendly food choices and their potential to reduce greenhouse gas emissions and support the related SDGs. The paper reports a field experiment that tests the effectiveness of two social norms in a real-life setting based on revealed preferences. The study distinguishes between the widely researched descriptive norms and guessed norms, the latter being tested in this context for the first time. While descriptive norms communicate typical patterns of behavior (e.g., 50% of canteen visitors choose vegetarian meals), guessed norms are determined by the individual's best guess about the norm in a specific context. The results confirm a remarkable nudging effect of guessed norms: The higher the presumed proportion of vegetarian dishes sold, the lower the probability of choosing a vegetarian dish. Surprisingly, this effect is independent of the respective norm specification (meat or vegetarian norm). The paper provides advice for policy makers about when and how to use guessed norms.
Keywords: 330; climate-friendly behavior; field experiment; guessed norm; nudging; social norms